Design of Intelligent Pedestrian and Vehicle Guidance System for Zebra Crossing Based on Millimeter Wave Radar. (September 2020) - Guo, Peng; Xiang, Hong; Wu, Shengguang; Pu, Tian; Chen, Dongyang
Abstract: In order to protect the life safety of the pedestrian and strengthen the intelligent management of urban traffic, this paper's proposes is a set of low-cost and easy-to-install intelligent transportation pedestrian and vehicle guidance system. The system can be applied to the non-crossroads zebra crossing. On the premise of ensuring the safety of crossing pedestrians, it would reduce the waiting time of vehicles when there are no pedestrians or scattered pedestrians passing by, to improve the vehicle traffic rates and avoid the traffic accidents about people and vehicles snatch the right of way, so as to effectively guide pedestrians and vehicles to pass. The system uses STM32L431RCT6 microcontroller as the main control chip, uses millimeter wave radar technology to monitor the number of pedestrians in front of the zebra crossing, intelligently controls the time of pedestrian passing, and coordinate the traffic lights on both sides of the road for countdown display by Lora, and switches the traffic status of vehicles and pedestrians, for realize the function of traffic command. At the same time, the system will automatically upload the number of pedestrian to OneNET, providing access and management interface for superior applications, so that the transportation department can master the travel rules, and provides travel data for the construction of smart city. The system also can receive data returned from OneNET, and flexibly control the time of pedestrian passing at that moment.